Narasi Pada Episode Mengenal Syi’ah Sebagai Bentuk Pelanggaran Standar Program Siaran Dalam Program Khazanah Trans7 (Studi Peraturan Pengawasan Pertelevisian Oleh Komisi Penyiaran Indonesia) - Agung, I Putu Suhada; Kris, Desi (Seni Media Rekam ISI Surakarta, 2014)
Indonesian Broadcasting Commission has an important role in the world oftelevision broadcasting. KPI create P3SPS that should be done and implemented bytelevision workers on Indonesian television according with Law No. 32 In 2002,KHAZANAH an Islamic program TRANS | 7 which received a reprimand from the KPI,episode Mengenal Syi’ah. Narrative that read maked a lot of controversy from thepublic and Syi’ah groups. Many residents complained to the KPI for give sanction toKHAZANAH. The purpose of this study to determine a infraction of broadcast standardprogram in KHAZANAH program, as well as knowing the KPI measures to providewarning in accordance with applicable law. The method used in this study is qualitativemethods, which will be presented descriptively; accurately depict the actual situation,the data collect from interviews, observation, and documentation. The result obtainedin this study is to know that the true treasures in infraction of applicable SPS and stepsof KPI to carry out his duties as a regulator. Continually look at episode MengenalSyi’ah which opinion publik and IJABI figure contravene broadcast content. KPI heldmediation between KHAZANAH and IJABI. Based on the research conducted, whichwas read on episode Mengenal Syi’ah caused controversy in the community, especiallythe Syi’ah group. The results of the mediation, a decision that KHAZANAH will providean opprtunity to IJABI give right of reply in the next episode, which is MencintaiRasulullah.Kata Kunci : syi’ah, narasi, kontroversi, mediasiIndonesian Broadcasting Commission has an important role in the world oftelevision broadcasting. KPI create P3SPS that should be done and implemented bytelevision workers on Indonesian television according with Law No. 32 In 2002,KHAZANAH an Islamic program TRANS | 7 which received a reprimand from the KPI,episode Mengenal Syi’ah. Narrative that read maked a lot of controversy from thepublic and Syi’ah groups. Many residents complained to the KPI for give sanction toKHAZANAH. The purpose of this study to determine a infraction of broadcast standardprogram in KHAZANAH program, as well as knowing the KPI measures to providewarning in accordance with applicable law. The method used in this study is qualitativemethods, which will be presented descriptively; accurately depict the actual situation,the data collect from interviews, observation, and documentation. The result obtainedin this study is to know that the true treasures in infraction of applicable SPS and stepsof KPI to carry out his duties as a regulator. Continually look at episode MengenalSyi’ah which opinion publik and IJABI figure contravene broadcast content. KPI heldmediation between KHAZANAH and IJABI. Based on the research conducted, whichwas read on episode Mengenal Syi’ah caused controversy in the community, especiallythe Syi’ah group. The results of the mediation, a decision that KHAZANAH will providean opprtunity to IJABI give right of reply in the next episode, which is MencintaiRasulullah.Kata Kunci : syi’ah, narasi, kontroversi, mediasi